Comparison of the effect of the steel and polypropylene fibres on the flexural behaviour of recycled aggregate concrete beams. (February 2021) - Karimipour, Arash; Ghalehnovi, Mansour
Abstract: Improving the flexural and shear performance of reinforced concrete (RC) beams plays a vital role in controlling the seismic behaviour of concrete structures. In this research, the flexural behaviour of RC beams made with recycled coarse aggregate (RCA), steel fibres (SF) and polypropylene fibres (PPF) are studied. A total of 54 RC beams with a cross-section 150 mm wide, 200 mm high, and a length of 1500 mm, with different transverse reinforcement spacing, are manufactured and tested. RCA from a building demolish is used as a replacement of natural coarse aggregate (NCA) at 0%, 50% and 100% (in term of mass). Moreover, SF and PPF are added to improve the flexural behaviour of the beams at 0%, 1% and 2% (in terms of volume). Specimens are tested under a four-point bending setup. In these tests, maximum flexural capacity, maximum deformation at mid-span of beams, ductility and the stiffness of specimens are measured. It was found that the influence of PPF on improving the flexural capacity of RC beams is higher than those made by SF; however, the effect of SF on deformation is more significant.